(untitled) (Medico Legal Update, 2021)
Background: The use of Endoscope is increasing for otologic surgery because it is providing anew perspective on the intricate anatomy of the middle ear. Study Design: Cross sectional study. Objective Evaluation of outcomes of endoscopic aidedtranscanal underlay tragal cartilegeMyringoplasty. Patients and Method: This were aprospective clinical study included Fifteen patients who were operated on for chronic otitis media (COM) and their data and findings. All operations and surgical procedures were performed only with the use of a tragal cartilage graft, lining, and total transcanal endoscopic access. We assessed the postoperative graft up-taking rate and assessed hearing at 6-8 weeks. Results and Discussion: Out of the 15 patients (9 female and 6 male) the graft take rate was 86% and the comparison of pre and postoperative mean AB gap revealed that the mean AB gap was 31 dB preoperatively while it changed (improved) to 16 dB at 6 to 8 weeks postoperatively, with a statistically significant difference (P<0.05). Conclusions: Endoscopic Myringoplastyis minimally invasive, effective and safe procedure with good success rate and short duration.